Globalization and education : integration and contestation across cultures - Stromquist, Nelly P.; Monkman, Karen (Lanham, Md. Rowman & Littlefield, 2000)
With increased opportunities for interaction and learning, education around the world is becoming transformed. These essays strive to provide a thorough examination of the impact these changes are having on how education is defined, whom it serves, and how it is assessed around the world. Topics incl: -- Conceptual issues: Globalization and internationalism; educational reform; curriculum inquiry. -- Globalization impact in educational sectors: European & South African Universities; community colleges; labor markets, gender, schooling & work; Adult education. -- Case Studies of Globalization Impacts: Commonwealth Caribbean; Japan; Lesoto; Mexico; South Africa; Malaysia; Australia.
Includes bibliographical references and index.
Keywords: Education -- Cross-cultural studies -- Economic aspects; Education -- Cross-cultural studies -- Social aspects; Education and globalization -- Cross-cultural studies